Dunia Anomali Dominasi Wanita: Pesan Moral dalam Iklan Djarum 76 versi Jin Takut Istri - Robingun Suyud El Syam; Alfan Nurngain (Lembaga Pengembangan Kinerja Dosen, 2023)
This study aims to reveal the anomaly of female domination: the moral message in Djarum 76 advertisement version of the genie is afraid of the wife, by representing something that is not visible on the surface. This article is a qualitative descriptive research type with Roland Barthes' semiotic analysis based on Stuart Hall's representation theory. Primary data through observation of text and audio-visual images from advertisements, and secondary data from relevant literature, then analyzed based on the concept of The Codes of Television. The results of the study show: in the Djarum 76 advertisement, the version of the genie is afraid of his wife, builds the image that men are afraid of their wives, which can be seen from the activities, sounds, expressions, camera techniques, and existing ideology. This anomaly is a reality that occurs a lot in the reality of society where a household is dominated by the wife. The research implication, narrative experience brings the consumer's mood to the narrative which is carried as a moral message. More specific research is needed to reveal the atmosphere of the relationship built on the research focus.